The Voice of Water: Belajar dari Desa Cikurubuk Buahdua Sumedang - Dinn Wahyudin; Edi Setiadi; Evan Firdaus (Bandung Conference Series: Economics Studies, 2024)
Abstract. Cikurubuk Village, which is located in Buahdua Sub-district, Sumedang Regency, has invaluable wealth in the form of abundant water sources spread over 10 points of the village area. So that it becomes a source of life for the people in the Cikurubuk Village area and its surroundings. This considerable natural potential can be empowered in the agricultural sector. Currently, there are problems with subsidized fertilizers, so farmers must continue to innovate in dealing with them. Organic farming is one of the proposed solutions. The Cikurubuk community's awareness of the need for healthier foodstuffs, namely organic foodstuffs, is expected to grow. Community service activities are carried out by a team of lecturers and students, and the writing of this article uses an analytical descriptive method. The results of community service activities are in the form of a business plan for developing organic agricultural cultivation consisting of making organic fertilizer, pre-harvest implementation, post-harvest implementation, marketing and business analysis per farmer group. With the gradual development of sustainable agriculture, it is hoped that farmers can change their mindset so that they do not continue to depend on government subsidized fertilizers which are increasingly difficult to obtain and at high prices. Abstrak. Desa Cikurubuk yang terletak di Kecamtaan Buahdua Kebupaten Sumedang, memiliki kekayaan yang tak ternilai yaitu berupa melimpahnya sumber mata air yang tersebar 10 titik wilayah desa. Sehingga menjadi sumber kehidupan bagi masyarakat yang ada di wilayah Desa Cikurubuk dan sekitarnya. Potensi alam yang cukup besar tersebut dapat diberdayakan pada sektor pertanian. Saat ini terdapat permasalahan pupuk subsidi sehingga para petani harus terus berinovasi dalam menghadapinya. Pertanian organik merupakan salah satu usulan solusinya. Kesadaran masyarakat Cikurubuk terhadap kebutuhan bahan makanan yang lebih sehat yakni bahan pangan organik diharapkan akan semakin tumbuh. Kegiatan pengabdian masyarakat dilakukan oleh tim dosen dan mahasiswa, dan penulisan artikel ini menggunakan metode deskriptif analitik. Hasil kegiatan pengabdian berupa rencana usaha pengembangan budidaya pertanian organik yang terdiri dari pembuatan pupuk organik, pelaksanaan pra-panen, pelaksanaan pasca-panen, pemasaran dan analisis usaha per kelompok tani. Dengan pengembangan pertanian yang berkelanjutan secara bertahap, diharapkan para petani dapat mengubah pola pikir agar tidak terus bergantung pada pupuk subsidi pemerintah yang semakin hari semakin susah didapatkan dan dengan harga yang mahal.